Quantum Bayesianism: Interpretation of Probability in Quantum Mechanics - Loso Judijanto (Yayasan Adra Karima Hubbi, 2025)
Quantum mechanics presents challenges in understanding probability, which is often seen as a measure of uncertainty in quantum systems. Quantum Bayesianism (QBism) is an alternative interpretation that considers probability as an observer's subjective belief, not as an objective representation of the state of the system. This study aims to delve deeper into the role of probability in quantum mechanics through the perspective of QBism. This study aims to examine the differences between Quantum Bayesianism and traditional quantum probability interpretations, as well as analyze how QBism can provide a more dynamic understanding of probability in quantum experiments. The methods used include literature analysis to identify publication trends related to QBism as well as case studies of quantum experiments that show the application of subjective probability theory. Data is obtained from various scientific sources and the latest publications in the field of quantum physics. The results show that Quantum Bayesianism provides a more flexible and subjective approach to probability, which allows probabilities to be calculated based on the observer's beliefs and can change according to the information obtained. The study also confirms that more and more researchers are adopting QBism in their research, replacing the more traditional view of objective probability. The study concluded that QBism offers a more relevant and applicable view of probability in quantum mechanics. Although there are still limitations in practical application, QBism opens up new opportunities in the understanding and development of quantum technology in the future.